Differences in scar lesion formation between radiofrequency and cryoballoon in atrial fibrillation ablation: a comparison study using ultra-high-density mapping. Issue 2 (12th October 2018) - Ruiz-Granell, Ricardo; Ballesteros, Gabriel; Andreu, David; Erkiaga, Ane; Ferrero-De-Loma-Osorio, Angel; Ramos, Pablo; Martínez-Brotons, Angel; Vives-Rodríguez, Enrique; Izquierdo-de-Francisco, Maite; García-Bolao, Ignacio
Abstract: Aims: Atrial fibrillation (AF) recurrence after pulmonary vein isolation (PVI) is usually associated to conduction gaps in pulmonary veins (PVs). Our objective was to characterize gaps in patients with recurrences after a first radiofrequency (RF) or cryoballoon (CB) PVI procedure, using a high-density mapping (HDM) system. Methods and results: Fifty patients with AF recurrence after a first PVI procedure (pre-RF 25 patients; pre-CB 25 patients) were included at two centres. Activation map (AM) and voltage map (VM) of the left atrium and PVs were built using the HDM Rhythmia® system. Superior PVs were reconnected more frequently in both groups. Right PVs were reconnected more frequently in pre-RF patients. Pre-RF patients had more reconnected veins than pre-CB patients (mean ± standard deviation: 3.00 ± 0.96 vs. 1.88 ± 1.13; P  < 0.001) and more gaps (4.84 ± 2.06 vs. 2.16 ± 1.49; P  < 0.001). Gaps in the VM were wider in pre-CB patients (16.5 ± 9.5 mm vs. 12.1 ± 4.8 mm; P  = 0.006). There was a gap in 179 of the 800 PV segments analysed (22%); 52% were identified in both AM and VM maps; 39% only in the AM and 8% only in the VM. The highest sensitivity and specificity for gap detection was obtained with VM in pre-CB patients and with AM in pre-RF patients. Conclusion: In conclusion, HDM seems to be a useful and precise tool to detect conduction gaps after a first PVI procedure. The anatomical pattern and location of gaps depends on the technique used previously, usually being multiple, smaller, and better detected by AM after RF, and fewer, wider, and better detected by VM after CB.